2009
DOI: 10.1029/2009gl039737
|View full text |Cite
|
Sign up to set email alerts
|

First Satellite Observations of Meteoric Smoke in the Middle Atmosphere

Abstract: [1] This work describes the first remote observations of meteoric smoke particles (MSPs) from satellite, by the Solar Occultation For Ice Experiment (SOFIE) onboard the Aeronomy of Ice in the Mesosphere (AIM) platform. The measurements show a layer of MSPs from roughly 35 to 85 km altitude, and indicate a seasonal cycle with reduced MSP abundance during polar summer. The measurements agree favorably with model results, and confirm that MSP transport by the global meridional circulation causes the dramatic redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
93
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 21 publications
10
93
0
Order By: Relevance
“…I E MSPs occur in a 126 weak plasma and so a small fraction are charged by electron attachment, which enables 127 them to be detected using rocket-borne Faraday cup detectors (Plane, et al, 2014, Rapp, et 128 al., 2012, Robertson, et al, 2014. These detectors can be coupled to photo-ionisation flash 129 lamps so that neutral particles can be detected simultaneously (Rapp, et al, 2012 observed by measuring their optical extinction using the SOFIE spectrometer on the AIM 137 satellite ), but the composition of the particles are not well constrained 138 (Hervig, et al, 2009 …”
Section: Meteoric Smoke Formation and Properties 107mentioning
confidence: 99%
“…I E MSPs occur in a 126 weak plasma and so a small fraction are charged by electron attachment, which enables 127 them to be detected using rocket-borne Faraday cup detectors (Plane, et al, 2014, Rapp, et 128 al., 2012, Robertson, et al, 2014. These detectors can be coupled to photo-ionisation flash 129 lamps so that neutral particles can be detected simultaneously (Rapp, et al, 2012 observed by measuring their optical extinction using the SOFIE spectrometer on the AIM 137 satellite ), but the composition of the particles are not well constrained 138 (Hervig, et al, 2009 …”
Section: Meteoric Smoke Formation and Properties 107mentioning
confidence: 99%
“…Among these are the nucleation of mesospheric ice particles (e.g., Rapp and Thomas, 2006), the mesospheric metal chemistry , the D-region charge balance (e.g., Rapp and Lübken, 2001), the heterogeneous formation of water vapour in the mesosphere (Summers et al, 2001), and even the nucleation of polar stratospheric cloud particles which play a major role in the formation of the ozone hole (e.g., Voigt et al, 2005). While some progress regarding the experimental investigation of these atmospheric trace species has been made over the past years with sounding rockets (e.g., Schulte and Arnold, 1992;Gelinas et al, 1998;Horányi et al, 2000;Rapp et al, 2005;Lynch et al, 2005;Barjatya and Swenson, 2006;Amyx et al, 2008;Strelnikova et al, 2009;Rapp et al, 2010), incoherent scatter radars Strelnikova et al, 2007;Fentzke et al, 2009), satellites (Hervig et al, 2009(Hervig et al, , 2012, and laboratory studies (Saunders and Plane, 2006), much of our knowledge about these particles still relies on model results (e.g., Hunten et al, 1980;Gabrielli et al, 2004;Megner et al, 2006Megner et al, , 2008Bardeen et al, 2008). Among other things, very little is still known about the physical and chemical properties of MSPs such as their composition and their electrical and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…These MSPs are particles, which originate from extraterrestrial matter that is injected into the atmosphere by evaporating meteors (Rosinski and Snow, 1961;Megner et al, 2006). The existence of these MSPs was proven by in situ measurements on sounding rockets (e.g., Havnes et al, 1996;Rapp et al, 2012), by spectrometers on board satellites (Hervig et al, 2009) and by means of incoherent-scatter radars (Strelnikova et al, 2007). MSPs have effects on the nucleation of ice particles in the mesosphere (e.g., Wilms et al, 2016, and references therein) and influences on the ionospheric charge balance Baumann et al, 2013;Plane et al, 2014;Asmus et al, 2015) and ion chemistry (Baumann et al, 2015) of the D region.…”
Section: Introductionmentioning
confidence: 99%